TROSY NMR with a 52 kDa sugar transport protein and the binding of a small-molecule inhibitor. (June 2014) - Kalverda, Arnout P.; Gowdy, James; Thompson, Gary S.; Homans, Steve W.; Henderson, Peter J. F.; Patching, Simon G.
Abstract Using the sugar transport protein, GalP, from Escherichia coli, which is a homologue of human GLUT transporters, we have overcome the challenges for achieving high-resolution [15N-1H]- and [13C-1H]-methyl-TROSY NMR spectra with a 52 kDa membrane protein that putatively has 12 transmembrane-spanning α-helices and used the spectra to detect inhibitor binding. The protein reconstituted in DDM detergent micelles retained structural and functional integrity for at least 48 h at a temperature of 25 °C as demonstrated by circular dichroism spectroscopy and fluorescence measurements of ligand binding, respectively. Selective labelling of tryptophan residues reproducibly gave 12 resolved signals for tryptophan 15N backbone positions and also resolved signals for 15N side-chain positions. For improved sensitivity isoleucine, leucine and valine (ILV) methyl-labelled protein was prepared, which produced unexpectedly well resolved [13C-1H]-methyl-TROSY spectra showing clear signals for the majority of methyl groups. The GalP/GLUT inhibitor forskolin was added to the ILV-labelled sample inducing a pronounced chemical shift change in one Ile residue and more subtle changes in other methyl groups. This work demonstrates that high-resolution TROSY NMR spectra can be achieved with large complex α-helical membrane proteins without the use of elevated temperatures. This is a prerequisite to applying further labelling strategies and NMR experiments for measurement of dynamics, structure elucidation and use of the spectra to screen ligand binding.